Transverse Spin Structure Function g2x, Q2. (27th June 2013) - Bagherpour, H.; Saeedhosseini, M.
Abstract : The transverse spin-dependent nucleon structure functiong 2 x, Q 2 at largeQ 2 is computed within the Wandzura-Wilczek relation, using NLOg 1 fit. Also we investigate the twist-3 contribution ofg 2 x, Q 2 via calculatingd 2 . It turns out that although the twist-3 part ofg 2 x, Q 2 can be negligible for DIS processes, it has a significant value in resonance region.